Parafoveal preview benefit in a conflicting sentential context: Evidence from ERPs - Li, Nan; Li, Gantang; Wang, Suiping (Frontiers in Psychology, 2022)
In natural reading, the reader’s processing of a word starts when the word is located in parafoveal vision. Relative to a situation with an invalid preview, fixations are significantly shorter after a fully valid, identical preview. Although research on the identity preview benefit has been ongoing for more than 40 years, the mechanism of this preview benefit, the level of lexical processing it occurs, and its relationship to the sentential context remain unclear. This study employed EEG brain component analysis technology to address these questions in Chinese sentence reading. We manipulated the sentential context to make the target word plausible or not plausible with the sentence and manipulated the target word present or not present in preview. EEG results showed that the identity preview benefit can affect not only the early preview positivity, reflecting the early orthographic processing of words, but also the N400 and LPC components, reflecting the late and in-depth semantic processing of words. Conflicting sentential context, in which the target word is implausible and cannot be integrated into the sentence, can interfere temporarily with these processes. These findings suggest that in the process of sentence reading, an identical preview word can promote the subsequent reading process at multiple levels, and its role is modulated by contextual information.